Hydrogeological Features of Mount Fuji and the Surrounding Area, Central Japan: An Overview - Adikari, Danda Pani (Journal of Institute of Science and Technology, 2015)
Mount Fuji (3776 m), Japan's highest mountain and one of the world's most picturesque stratovolcano was studied to give an overview of its hydrogeological features. The mountain was made from voluminous lava flows and pyroclastic materials produced through three generations of volcanic activities. The volcanic products, characterized by abundant pore spaces and fractures, play a role as productive aquifers by absorbing and storing rain and snow melt as groundwater and releasing it over a long period. Its foot slopes contain abundant water with Fuji-Five-Lakes in the north and hundreds of springs with enormous discharge to the south, leaving the upper slopes dry. Approximately 2.2 billion tons of rain and snow fall annually at Mt. Fuji, and 4.5 million tons of groundwater is stored each day in average. The total amount of spring or groundwater discharge from Mt. Fuji is estimated at 6.55 x 106 m3/day and that in its southwestern slopes is 1.76 x 106 m3/day. Rain and snow falling above the altitude of 1,000 m is their main source of recharge. The water provides vital resources for the people living around it; however, over exploitation of this resource have already caused some decline in its quality and quantity. Journal of Institute of Science and Technology, 2014, 19(1): 96-105